DETERMINAN EFEKTIVITAS AUDITOR INTERNAL PEMERINTAH (Studi Pada Kantor Inspektorat Provinsi Maluku Utara) - Zamzam, Irfan; Mahdi, Suriana AR (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
This study examines the determinants of the effectiveness of internal auditors at the Office of the Inspectorate of North Maluku. Specifically, this study tests; influence of professional expertise, quality of work, independence, perceived career path and top management influence of internal auditor on the effectiveness of internal audit. Analysis was conducted by using multiple regression analysis from 43 respondents. The results showed that; Professional expertise, quality of work, independence and career path affect the effectiveness of internal audit while top management support does not influence the effectiveness of internal audit.